Bioinformatic exploration of structural and functional features of genes associated with rare diseases. - Concha-Trochez, Paola Andrea (2022)
Objective: Rare diseases have been related to rare variants with a high penetrance for many genes, however, these genes that cause rare diseases are not necessarily rare genes, because they are related to several essential pathways for cells, and in many cases are common for rare and common diseases. Consequently, it is possible to propose that the genes causing rare diseases could be related to fundamental processes or critical regions in the human genome. In this study, we explore the genes causing rare diseases based on a description of their structure and function for the identification of critical functional processes and a gene regulatory context for their association with specific diseases that can be explored. Materials and methods: The genes causing rare diseases, extracted from the ORPHANET and OMIM database, were explored to identify if there is any similarity within their structural and functional characteristics. In addition, a systematic review of the literature is carried out in order to capture the most relevant diseases found in the bioinformatic analysis. Results: Here we report that the genes that cause rare diseases are related to fundamental cellular processes, whose genes are found in genomic regions with a high density of repeats. Our data show metabolism, disease and cellular processes, as the most frequent categories associated with genes causing rare diseases, which include critical pathways for cell viability such as glycosaminoglycan degradation, primary immunodeficiency or cell junctions. Conclusions: Our results establish a general description of the basic structural characteristics of genes related to rare diseases, in addition to establishing key processes that describe rare diseases in cellular contexts common to other diseases, these processes being important for future explorations.